Competitive Advantage Strategy in Yanara Laundry Business in Facing Competition Between Laundry Service Businesses in Bandar Lampung - Aldi Dinanjar; M. Oktaviannur; Dora Rinova; Irsandi, Irsandi (International Journal of Economics, Business and Innovation Research, 2024)
In a competitive business world, every company needs to develop an effective competitive strategy. This is due to the increasingly tight competition in the market. The main goal of today's business is to create and add value to customers, so that they can win the hearts of consumers and gain a competitive advantage. By implementing the right strategy, businesses can control a larger market share and increase their competitiveness. This strategy includes a deep understanding of customer needs and wants, as well as the ability to adapt to market changes and offer unique and valuable products or services. The strategy has great potential to occur and requires top management decisions and significant resource allocation from the company. The laundry business is one form of small and medium enterprises (SMEs) in the service sector that is currently experiencing rapid development. This business offers laundry services that include the process from washing to drying, as well as completion by returning clothes to consumers according to expectations. The method used in this study is quantitative. The results of the study show that Yanara Laundry can achieve competitive advantage through the implementation of differentiation strategies, cost leadership, and the use of digital technology.